Systemic Financial Crises How to Fund Resolution - Schich, Sebastian (OECD Publishing, 2011)
Systemic financial crises are a recurrent phenomenon, and despite regulatory efforts they are likely to occur again. This report compares the ex ante funding of deposit insurance schemes in a selection of countries, highlighting the "funding gap" left by these arrangements in the recent systemic financial crisis. To fill that gap, different approaches have been adopted across countries in the recent crisis. Where support for the financial sector was provided as part of policy response to the crisis, new taxes have been adopted to generate revenues ex post, although the specific approaches have differed. While there is no single solution in this regard, this report finds that ex ante funded systemic crisis resolution funds, together with strengthened failure resolution powers, are in principle adequate to help fill the gap. JEL Classification: E44, G01, G21, G28, E61, H21. Keywords: systemic financial crisis, systemic crisis resolution fund, deposit insurance, financial activities taxes, ex ante versus ex post funding
Keywords: Finance and Investment